Preliminary determination of the salinity profile during neap-spring tides of the Sg. Baru Estuary, Perlis / Faridah Hanum Badrun - Badrun, Faridah Hanum (Unit of Research, Development and Commercialization (URDC),UiTM Perlis, 2004)
This preliminary study was undertaken to examine the mixing dynamics during neap and spring tide at the Sg. Baru estuary, Perlis. Variation between temperature, depth and salinity were recorded to determine water column stability during the semi-diurnal tidal conditions. The results showed that vertical mixing occurred during spring tide and a salinity gradient persisted during neap tide. Although the water column is relatively shallow, salinity and temperature data indicate that lower salinity corresponds to higher temperature. Key words :salinity estuary, neap tide, spring tide